2b−c |
a |
cosC |
cosA |
2sinB−sinC |
sinA |
cosC |
cosA |
即 2sinBcosA=sinAcosC+sinCcosA,故2sinBcosA=sin(A+C)=sinB,…(4分)
∴cosA=
1 |
2 |
π |
3 |
(II)∵A=
π |
3 |
2π |
3 |
故函数y=
3 |
π |
6 |
3 |
π |
2 |
3 |
π |
6 |
∵0<B<
2π |
3 |
π |
6 |
π |
6 |
5π |
6 |
π |
6 |
1 |
2 |
故函数的值域为 (1,2]. …(14分)
2b−c |
a |
cosC |
cosA |
3 |
π |
6 |
2b−c |
a |
cosC |
cosA |
2sinB−sinC |
sinA |
cosC |
cosA |
1 |
2 |
π |
3 |
π |
3 |
2π |
3 |
3 |
π |
6 |
3 |
π |
2 |
3 |
π |
6 |
2π |
3 |
π |
6 |
π |
6 |
5π |
6 |
π |
6 |
1 |
2 |